A quantum chemical analysis of dependence of the protolytic properties of silica primary particles on their composition and spatial structure - Kravchenko, A.A.; Demianenko, E.M.; Filonenko, O.V.; Grebenyuk, A.G.; Lobanov, V.V.; Terets, M.I. (Поверхность, 2017)
High disperse silica is used as a sorbent and carrier of medical preparations in various branches of medicine, biotechnology etc. due to its physico-chemical properties, in particular, rather developed surface, chemical inertness, considerable adsorption capacity. The protolytic equilibrium of silica surface is to be examined, because the structure of its hydroxylic layer determines its properties. When silicic acid is polymerized, an increase in the molecular mass of the particles formed and the acidic properties of oligomers are changed.